INSTITUTIONALIZING PAIDEIA AS A BASIS FOR TEACHING AND THE UNIVERSITY - James Kennedy Campbell (Journal Analytica Islamica, 2021)
Understanding the history of the university/colleges, the roots of theu niversity within Islamic civilization provides a reminder of the moral mission of the university within Islamic societies but also should be taken seriously in so-called western debates about the normative nature of higher education and its cultural and institutional roots. Not  only is this influenceof historical interest but it is also critical to understanding the moral dimension to the history of the university and opens us up to engaging in dialogue over the very meaning of our higher educational institutions and their practices.